The Tales of the Heike - Watson, Burton, 1925-2017; Shirane, Haruo, 1951- (New York Columbia University Press, 2006)
Written in the mid-thirteenth century, this book chronicles the epic Genpei war, a civil conflict that marked the end of the power of the Heike clan and changed the course of Japanese history. It depicts the emerging world of the medieval samurai